LANGUAGE KINSHIP IN THE LANGUAGE USED BY THE PANJALIN VILLAGE COMMUNITY (SYNCHRONOUS COMPARATIVE) - Atristha Indah Listiyani (STKIP Muhammadiyah Kuningan, 2023)
The purpose of this study is to analyze and study the level of language kinship and synchronic comparative forms in the language used by the people of Panjalin Kidul Village. The method used is qualitative. Data collection techniques used are observation, interviews, and documentation. The results of this study show that there is a kinship relationship between the Javanese and Sundanese languages ​​used in the daily communication of the people of Panjalin Kidul Village. The results of the study found 160 vocabularies consisting of Javanese and Sundanese in Panjalin Kidul Village. From the synchronic comparative approach, there are 72 data based on the symptoms of variations in the sounds of the language. It consists of 30 data on synonym sound variations and 42 data on homonym sound variations. The language relatedness level is 81% and the error term for determining the relatedness percentage is 9.4. This shows that there is a kinship relationship between the Javanese and Sundanese in Panjalin Kidul Village.